Targeting Plasmodium ligands on mosquito salivary glands and midgut with a phage display peptide library - Ghosh, Anil K.; Ribolla, Paulo E. M. [UNESP]; Jacobs-Lorena, Marcelo (Proceedings of the National Academy of Sciences, 2001)
Despite vast efforts and expenditures in the past few decades, malaria continues to kill millions of persons every year, and new approaches for disease control are urgently needed. To complete its life cycle in the mosquito, Plasmodium, the causative agent of malaria, has to traverse the epithelia of the midgut and salivary glands. Although strong circumstantial evidence indicates that parasite interactions with the two organs are specific, hardly any information is available about the interacting molecules. By use of a phage display library, we identified a 12-aa peptide-salivary gland and midgut peptide 1 (SM1)-that binds to the distal lobes of the salivary gland and to the luminal side of the midgut epithelium, but not to the midgut surface facing the hemolymph or to ovaries. The coincidence of the tissues with which parasites and the SM1 peptide interact suggested that the parasite and peptide recognize the same surface ligand. In support of this hypothesis, the SM1 peptide strongly inhibited Plasmodium invasion of salivary gland and midgut epithelia. These experiments suggest a new strategy for the genetic manipulation of mosquito vectorial capacity.
Keywords: peptide; peptide library; peptide sm1; unclassified drug; controlled study; hemolymph; hypothesis; midgut; nonhuman; ovary; parasite migration; phage display; Plasmodium; priority journal; protein binding; salivary gland; Animals; Anopheles; Binding Sites; Female; Intestines; Peptide Library; Plasmodium berghei; Salivary Glands; Protozoa